Single bacteria spore encapsulation through layer-by-layer self-assembly of poly(dimethyldiallyl ammonium chloride) and silica nanoparticles for self-healing concrete - Xiao, Xi (2023)
Self-healing of cracks improves durability and reduces maintenance of concrete. Microbial induced calcite precipitation is a novel approach to engage self-healing in concrete, and bacteria spores are protected from direct contact with the surrounding cement matrix to maintain their viability. This study proposes a novel single bacteria spore capsule via layer-by-layer (LbL) self-assembly of poly(dimethyldiallyl ammonium chloride) and silica nanoparticles to enhance the consistency of healing as well as to minimize the negative impact on the mechanical properties of the resulting concrete. The resulting single bacteria spore capsule has a size of 1 μm and the inclusion of the capsules dose not compromise the compressive strength of the matrix. Cement paste incorporating the capsules shows complete closure of large crack of few hundred microns and complete recovery of transport property. Healing products are observed along the entire crack from the surface to the interior.